Pharmacokinetics and Toxicity in Rats and Monkeys of coDbait: A Therapeutic Double-stranded DNA Oligonucleotide Conjugated to Cholesterol - Anne Schlegel; Cyril Buhler; Flavien Devun; Céline Agrario; Saïk Urien; François Lokiec; Jian-Sheng Sun; Marie Dutreix (Molecular Therapy: Nucleic Acids, 2012)
Increased DNA repair activity in cancer cells is one of their primary mechanisms of resistance to current radio- and chemotherapies. The molecule coDbait is the first candidate in a new class of drugs that target the double-strand DNA break repair pathways with the aim of overcoming these resistances. coDbait is a 32-base pair (bp) double-stranded DNA molecule with a cholesterol moiety covalently attached to its 5′-end to facilitate its cellular uptake. We report here the preclinical pharmacokinetic and toxicology studies of subcutaneous coDbait administration in rodents and monkeys. Maximum plasma concentration occurred between 2 to 4 hours in rats and at 4 hours in monkeys. Increase in mean AUC0–24h was linear with dose reaching 0.5 mg·h/ml for the highest dose injected (32 mg) for both rats and monkeys. No sex-related differences in maximum concentration (Cmax) nor AUC0–24h were observed. We extrapolated these pharmacokinetic results to humans as the subcutaneous route has been selected for evaluation in clinical trials. Tri-weekly administration of coDbait (from 8 to 32 mg per dose) for 4 weeks was overall well tolerated in rats and monkeys as no morbidity/mortality nor changes in clinical chemistry and histopathology parameters considered to be adverse effects have been observed.